Highland conqueror eaudiobook - Howell, Hannah (Murray Family, 2014)
Lady Jolene Gerard is running out of time—each moment she remains within the walls of Drumwich Castle she is in jeopardy. Her only chance lies with a prisoner chained to the dungeon walls, a Scotsman who, in return for freedom, helps Jolene and her young nephew escape her cousin's deadly snare. Pursued by murderous villains, Jolene is prepared to fight for her life. But in the arms of rugged Sigimor Cameron, she soon surrenders her heart . . . He was too late to save the Englishman to whom he owed a blood debt, but not the man's lovely sister. Stunned by his desire for the spirited English lass, Sigimor presses them on to safety, his enemies in dogged pursuit. And while sweet desire speaks a thousand words, the secret they long to share remains locked in a battle of stubborn pride. But when saving Jolene from his enemy leaves Sigimor no choice but to make her his wife, a bargain born of passion can only by sealed by the kiss of true love . . .